Enhancing Inhalation Therapy through Real-Time Monitoring of Inspiratory Airflow: An Experimental Study Using the Tokico Inhalation Monitor - Ohbayashi, Hiroyuki; Horikoshi, Seira; Ishizeki, Kazunori; Okada, Toyoko; Kudo, Sahori; Furuta, Osamu; Ariga, Mitsue (Scientific Research, New Technologies and Applications Vol. 2, 2024)
Background: Inhalation therapy is a pivotal treatment method for asthma and COPD, as indicated in major international guidelines. An inhalation pattern is conventionally communicated to each patient by imaging verbal expression; as such, inhalation instructions may be ambiguous. A new inspiratory air-flow velocity measurement monitor (Tokico Inhalation Monitor, TIM) can visualize real-time inhalation patterns. Purpose: The primary purpose of the study is to evaluate the usefulness of the TIM as a new type of patient education machine for inhalation instruction in routine clinical practice. Methods: After the responsiveness, accuracy, and reproducibility of the TIM were verified, the differences between conventional verbal inhalation imaging and real-time instructions using the TIM were evaluated. Six healthy subjects (mean age 59.7 ± 10.4 years, male-to-female ratio 3/3) were given various verbal images of the inhalation method, and then individually measured the pattern of air inhalation. Inhalation patterns using the real-time TIM and inhalation of conventional language images were compared using total inhalation volume and inhalation flow rate as indicators. The statistical significance level was set at 5%. Within-group comparisons were analyzed as nonparametric data using the Wilcoxon signed-rank test. Results: When the inhalation method was conveyed in words, the inhalation pattern differed depending on each subject’s interpretation. By self-adjusting with repeated inhalation exercises with the TIM, total inhalation increased significantly to 1.90 ± 0.28 (L) (p = 0.046, Wilcoxon signed-rank test), compared to the 1.66 ± 0.39 (L) obtained during verbal imaging, while maintaining an adequate maximum inhalation flow rate of 62.2 ± 14.5 (L/min). Conclusion: Using the TIM to perform inhalation exercises while drawing real-time inhalation patterns can increase the potential and effectiveness of self-regulating inhalation, thus making inhalation therapy more clinically useful. To achieve the benefits of TIM, more detailed investigations of long-term outcomes are needed to expand to larger sample sizes and more diverse populations for broader applicability.